Relationship between family functioning, parenting behaviour, self-efficacy, and gender on risky behaviour amongst adolescents in Kuala Lumpur, Malaysia - Mohd Hedzir, Annita (2018)
Adolescence is the developmental period marked by a rise in risk-taking behaviours. The high rate of adolescents’ involvement in risky behaviours in the past decades has created a vast amount of attention on the impact to their future. In Malaysia, the impact of risky behaviour has been alarming as evidenced by the media reports on baby dumping, unwanted pregnancies, drug addiction and juvenile delinquency. The increasing trend of adolescents’ involvement in risky behaviour may be associated with social- and self-factors. The current study was conducted to investigate the relationship between family functioning, parenting behaviours, self-efficacy, and gender on risky behaviours amongst adolescents in Kuala Lumpur, Malaysia. This quantitative study utilised a descriptive and correlational research design. Data were collected using self-administered questionnaires. A total of 411 adolescents aged 15 to 18 years were recruited as respondents. Six instruments were used namely the Family Perception Scale, the Parental Monitoring Scale, the General Self-Efficacy Scale, the Adolescent Alcohol and Drug Involvement Scale, the Adolescent Sexual Activity Index, and the Self-Reported Delinquent-Problem Behaviour Frequency Scale to measure the respective variables. Descriptive, bivariate, and multivariate statistics were used in analyses to address the specific objectives of the study. The study found that 12.6% of adolescents reported engagement in substance use, 47.2% in risky sexual behaviour, and 52.1% in delinquency. The independent t-test analysis showed that the proportion of male adolescents who engaged in substance use was higher compared to female. There were no significant differences between male and female in risky sexual behaviour and delinquency. Findings of this study showed that self-efficacy only moderated the relationship between parental monitoring and substance use, whereby the effect is strongest among adolescents with low self-efficacy, and weakest among adolescents with high self-efficacy. This suggested that there is low risky for adolescents to involve in substance use if the adolescent has higher level of self-efficacy. Meanwhile, gender only moderated the relationship between parental monitoring and risky sexual behaviour, whereby the effect is stronger among male adolescents compared to female adolescents. This suggested that male adolescents tend to involve more with risky sexual behaviour compared to female adolescents. The present study conclude that family functioning (family cohesion, communication), parenting behaviour (parental monitoring and parental involvement), self-efficacy and gender influence risky behaviours (substance use, risky sexual behaviour and delinquency) amongst adolescents in Kuala Lumpur. The findings has implication for parents as well as individuals and professional working with adolescents. Parental monitoring was significantly correlated with substance use thus parents were suggested to provide appropriate monitoring to increase awareness that their involvement is crucial in reducing adolescents’ substance use. They also need to be equipped with appropriate skills to establish high quality relationship with their adolescent children. The finding also call for intervention to provide adolescents with necessary skills to help them avoid being involved in risky behaviour.